Transcrippled subjectivity. The body/corpus of Lorenza Böttner (Anclajes, 2019)
In this work we will give an account of the process of subjective and artistic self-construction carried out by Lorenza Böttner (1959-1994), who, at an early age and due to an electric shock, loses both arms. His rejection of prosthetics and his interest in art will transform his body into a canvas and make known a performative and transgender subjectivity, assuming the name of Lorenza as an authorial figure. In addition, we are interested in analyzing how Lorenza Böttner has been recreated from literary fiction, taking as an example the chronicle by Pedro Lemebel, “Lorenza (las alas de la manca)” (1996) and the novel by Roberto Bolaño, Estrella distante (1996). We will also mention “Petra”, the mascot that Javier Mariscal made for the Paralympic Games of Barcelona (1992) that will become flesh in the body of Lorenza.
Keywords: Lorenza Böttner; Transgender; Crip theory; Queer; Diversity